(untitled) (REMUNOM, 2026)
Occurrences of lethal crimes, including homicides, have increased in recent decades in all cities. It is important to understand the dynamics of crime. This study aims to analyze the existence of spatial autocorrelation of income and homicide rates in Belém in the period from 2020 to 2022. It is a quantitative, documentary and descriptive research, with exploratory analysis of spatial data, of homicide occurrences in the period of 2020 to 2022 in Belém do Pará, Brazil. When evaluating the spatial autocorrelation of homicides in Belém using the Univariate Global Moran’s I, a positive and significant autocorrelation was found regarding homicide occurrences. When obtaining Bivariate Global Moran’s I for the variables “Income” and “hom”, positive spatial autocorrelation was found in all years. For the variables Income and Spatial Homicide Rate, a significant negative correlation was observed, except for the year 2021, in which autocorrelation was non-significant. It was concluded that there was spatial autocorrelation regarding the occurrences of homicide, as well as the correlation of the Income variable with the hom and TE variables. Using the Cluster Map, the presence of clusters can be observed in terms of high-high, low-low, high-low and low-high patterns in Belém and the district of Mosqueiro.